Efficient group signature scheme with revocation - Hong ZHONG; Cong-lin HUANG; Yan XU; Jie CUI (Tongxin xuebao)
A group signature scheme which combines the subset cover framework with Camenisch-Stadler scheme was proposed.This scheme allowed any group members’ entrance and revocation without changing other members’ secret key.Meanwhile,the scheme added a knowledge signature while registering,that realized coalition resistance.It is shown that the scheme not only has the characteristics of anonymity and no-relation,but also can resist conspiracy attacks,forgery attack and authority trap attack.As for efficiency,the scheme just slightly increases the length of group members’ certificates,with the signature and verification complexity remaining at constant level.